1993
DOI: 10.1002/1097-0142(19930915)72:6<1926::aid-cncr2820720622>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Dna flow cytometry and pathologic grading as prognostic guides in axillary lymph node-negative breast cancer

Abstract: Background. The recurrence or mortality rate of axillary lymph node‐negative invasive breast cancer has been associated with the tumor S‐phase fraction, which is measured by DNA flow cytometry. Because many of the studies that established this association were performed using frozen, pulverized tumor specimens, this association could not be tested for independence from the established prognostic factors of histologic and nuclear grading. Methods. Histologic, nuclear, and mitotic grades, DNA ploidy, and S‐phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
18
1
1

Year Published

1996
1996
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(23 citation statements)
references
References 27 publications
(1 reference statement)
3
18
1
1
Order By: Relevance
“…Tumour cell proliferation has been shown to be a prognostic marker in some reports (Remvikos et al, 1989;Bonetti et al, 1996;Chevillard et al, 1996), but data on its predictive value are conflicting. S-phase fraction, proliferating cell nuclear antigen and thymidine labelling index predict overall survival (Clayton, 1991;Fisher et al, 1991;Merkel et al, 1993) and response (Collecchi et al, 1996;Bottini et al, 1998;Nishimura et al, 2002), but not diseasefree survival (Bianchi et al, 1993;Pisansky et al, 1993;Tahan et al, 1993) in patients treated with primary surgery or chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Tumour cell proliferation has been shown to be a prognostic marker in some reports (Remvikos et al, 1989;Bonetti et al, 1996;Chevillard et al, 1996), but data on its predictive value are conflicting. S-phase fraction, proliferating cell nuclear antigen and thymidine labelling index predict overall survival (Clayton, 1991;Fisher et al, 1991;Merkel et al, 1993) and response (Collecchi et al, 1996;Bottini et al, 1998;Nishimura et al, 2002), but not diseasefree survival (Bianchi et al, 1993;Pisansky et al, 1993;Tahan et al, 1993) in patients treated with primary surgery or chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…5,10 There 10 Paraffin 165 P Ͻ 0.0001 a Muss 16 Frozen 101 51 NS NS NS NS Clark et al 11 Frozen 345 59 P ϭ 0.02 NS P ϭ 0.02 NS Clark et al 11 Paraffin 298 b NS NS Toikkanen et al 12 Paraffin 158 336 P ϭ 0.01 NS Sigurdsson et al 18 250 48 NS NS O'Reilly et al 19 Paraffin 136 c 96 NS Beerman et al 20 Frozen/paraffin 349 84 NS Keyhani-Rofagha et al 21 Paraffin 165 103 NS Winchester et al 22 Paraffin 257 80 NS NS Merkel et al 23 Paraffin 280 76 NS Balslev et al 13 Frozen 10 demonstrated DNA ploidy to have a prognostic significance in ER-positive tumors, but not in ER-negative tumors, in patients with stage I-III breast cancer. In the present study, multivariate analysis showed the prognostic significance of DNA ploidy, in terms of DFS, in ER-positive breast cancer specimens, but not in ER-negative breast cancer specimens.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] The prognostic value of DNA ploidy has also been extensively studied in Western women with node-negative breast cancer; however, the results have not been consistent. [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] Some studies have shown that patients with aneuploid tumors have a significantly worse clinical outcome, [9][10][11][12][13][14][15] whereas others have shown DNA ploidy to have no prognostic value. [16][17][18][19][20][21][22][23] A few studies have reported the relationship between DNA ploidy and the clinical outcome in Japanese patients with breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…When tested in multivariate analysis strategies, DNA ploidy failed to be an independent prognostic variable (26,27). Also, some investigators presented data that failed to show any prognostic significance of either S-phase (28 -30) or DNA ploidy (28,30,31). These findings are also well summarized in different breast cancer study reviews (32)(33)(34)(35)(36).…”
mentioning
confidence: 99%